PROFIL MOTIVASI BERPRESTASI SISWA SMA NEGERI 1 NGAMPRAH - Eneng Lia Fibriati; Euis Eti Rohaeti; Devy Sekar Ayu Ningrum (IKIP Siliwangi, 2022)
The purpose of this study was to describe the achievement motivation of class X students of SMA Negeri 1 Ngamprah. The subjects of this study consisted of 30 students of class X SMA Negeri 1 Ngamprah, while the sampling technique used purposive sampling technique, namely the technique of determining the sample with certain considerations, this study used quantitative descriptive research methods. The data collection technique is through interviews and observations, while the data collection tool used is the distribution of questionnaires using the grand theory indicators from Mc. Clelland. The results of the study obtained a picture of student achievement motivation, namely the need for achievement, which is 68.75% with a moderate categorization, where the need for power is 45.73% with a low categorization, and the need for affiliation (need for power). of affiliation) that is the need to obtain good social relations by 63.46% with moderate categorization. Based on the results of this study, it can be concluded that most of the students' achievement motivation is still classified as moderate, with an average of 64.33%.Keywords: Achievement Motivation, Students